Intensive vs. Standard Blood Pressure Control and Cardiovascular Risk: A Meta-Analysis of RCT Evidence Including the SPRINT Trial - Saeed, Yusra; Tariq, Haseeb; Fakhar, Amna; Chaudhary, Muhammad Oreed Aslam; Khan, Maryam Tufail; Irfan, Uzair (Indus Journal of Bioscience Research, 2025)
Background: Hypertension is a major modifiable risk factor for cardiovascular disease (CVD). While standard blood pressure (BP) control has traditionally targeted systolic BP below 140 mmHg, recent trials suggest that more intensive control may offer superior cardiovascular protection. This meta-analysis evaluates the impact of intensive versus standard BP control on major cardiovascular outcomes across randomized controlled trials (RCTs). Methods: A systematic literature search was conducted across PubMed, Cochrane Library, and ClinicalTrials.gov for RCTs published between January 2010 and March 2024. Studies comparing intensive (SBP <120 mmHg) and standard (SBP <140 mmHg) BP control and reporting cardiovascular outcomes were included. Data extraction and risk of bias assessment followed PRISMA 2024 and Cochrane ROB2 guidelines. Meta-analyses were performed using RevMan 5.4, and heterogeneity was assessed via the I² statistic. Results: Four RCTs involving 23,191 participants were included. Intensive BP control showed a non-significant reduction in cardiovascular events in one subgroup (RR = 0.58; 95% CI: 0.26–1.31; p = 0.19; I² = 98%) and a statistically significant reduction in another subgroup (RR = 0.78; 95% CI: 0.67–0.91; p = 0.002; I² = 0%). Risk of bias varied, with two trials demonstrating low risk and two showing high risk across multiple domains. Funnel plots indicated minimal publication bias but were limited by the small number of included studies. Conclusion: Intensive BP control may confer cardiovascular benefits over standard targets, particularly in rigorously conducted trials with low bias and consistent designs. However, heterogeneity and methodological limitations in certain studies caution against universal application. Further large-scale RCTs are warranted to confirm the long-term efficacy and safety of intensive BP targets across diverse populations.